Homozygous SCN1B variants causing early infantile epileptic encephalopathy 52 affect voltage‐gated sodium channel function. (26th April 2021) - Scala, Marcello; Efthymiou, Stephanie; Sultan, Tipu; De Waele, Jolien; Panciroli, Marta; Salpietro, Vincenzo; Maroofian, Reza; Striano, Pasquale; Van Petegem, Filip; Houlden, Henry; Bosmans, Frank
Abstract: We identified nine patients from four unrelated families harboring three biallelic variants in SCN1B (NM_001037.5: c.136C>T; p.[Arg46Cys], c.178C>T; p.[Arg60Cys], and c.472G>A; p.[Val158Met]). All subjects presented with early infantile epileptic encephalopathy 52 (EIEE52), a rare, severe developmental and epileptic encephalopathy featuring infantile onset refractory seizures followed by developmental stagnation or regression. Because SCN1B influences neuronal excitability through modulation of voltage‐gated sodium (NaV ) channel function, we examined the effects of human SCN1B R46C ( β1 R46C ), SCN1B R60C ( β1 R60C ), and SCN1B V158M ( β1 V158M ) on the three predominant brain NaV channel subtypes NaV 1.1 ( SCN1A ), NaV 1.2 ( SCN2A ), and NaV 1.6 ( SCN8A ). We observed a shift toward more depolarizing potentials of conductance–voltage relationships (NaV 1.2/ β1 R46C, NaV 1.2/ β1 R60C, NaV 1.6/ β1 R46C, NaV 1.6/ β1 R60C, and NaV 1.6/ β1 V158M ) and channel availability (NaV 1.1/ β1 R46C, NaV 1.1/ β1 V158M, NaV 1.2/ β1 R46C, NaV 1.2/ β1 R60C, and NaV 1.6/ β1 V158M ), and detected a slower recovery from fast inactivation for NaV 1.1/ β1 V158M . Combined with modeling data indicating perturbation‐induced structural changes in β1, these results suggest that the SCN1B variants reported here can disrupt normal NaV channel function in the brain, which may contribute to EIEE52.